Written corrective feedback from an ecological perspective: The interaction between the context and individual learners. (February 2019) - Han, Ye
Abstract: Previous research has identified a range of learner factors and contextual factors that mediate L2 learners' engagement with written corrective feedback (WCF). However, much remains to be known about how these factors impact individual learners' engagement with WCF in L2 classrooms. To address this issue, the paper draws upon the ecological perspective on language learning to discuss the data collected in a case study on Chinese university EFL students' engagement with WCF. Data were collected from multiple resources including students' writing, verbal reports, interviews, field notes, and class documents. While the context, ranging from the textual level to the broad sociocultural level, was found to provide resources that could afford learning, engagement hinged on whether students were able and willing to perceive and use those affordances. The findings suggest that learner engagement with WCF can be conceptualized as a process of perceiving and acting upon embedded learning opportunities afforded by WCF, and highlight the importance of establishing an alignment between affordances and learner agency to enhance individual students' engagement with written feedback. Highlights: The paper takes an ecological perspective on learner engagement with WCF. WCF, among other learning resources, are situated in the multi-layered context. Learner engagement with WCF is a process of perceiving and acting upon affordances. Multiple learner factors and contextual factors influence learner engagement with WCF. Engagement requires an alignment between learner agency and affordance in the context.